Challenges and Strategies in Enhancing Vocabulary Mastery among High School Students in English Language Classes - Fatin, Adilah Nurul; Jabu, Baso; Talib, Ahmad (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2026)
This study analyzes the challenges and strategies in enhancing English vocabulary mastery among high school students at UPT SMA Negeri 8 Makassar. The research involved ten students from grades X and XI, with data collected through semi-structured interviews. Findings show that students face significant challenges, including a lack of motivation, cognitive overload leading to forgetfulness, fear of making mistakes due to peer ridicule, limited practice opportunities, absence of teacher feedback, and restricted access to technology in class. To overcome these challenges, students actively employ self-initiated strategies, such as repetitive memorization, learning through English songs/movies/social media (TikTok, Instagram Reels), using mnemonic techniques, creating thematic word maps, playing informal vocabulary games during breaks, and participating in the English club (EFORS). Some also use apps like Duolingo. This study concludes that while students are resourceful, teachers must adopt more supportive, technology-integrated, and communicative methods to reduce anxiety and improve long-term retention.